2020
DOI: 10.3389/fendo.2020.587450
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane Extract Protects Islets From Serum-Deprivation Induced Impairments and Improves Islet Transplantation Outcome

Abstract: Islet culture prior to transplantation is a standard practice in many transplantation centers. Nevertheless, the abundant islet mass loss and function impairment during this serum-deprivation culture period restrain the success of islet transplantation. In the present study, we used a natural biomaterial derived product, amniotic membrane extract (AME), as medium supplementation of islet pretransplant cultivation to investigate its protective effect on islet survival and function and its underlying mechanisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…40 Our previous study also confirmed that the amniotic membrane extract contains multiple growth factors, including hepatocyte growth factor, epidermal growth factor, etc, which have protective effects on islet survival and function. 20 Therefore, compared with other prevascularization strategies, islet transplantation into PST on the liver surface may be independent of the additional administration of expensive growth factors 39,41,42 or other accessory cells (such as autologous adipose-derived stem cells or fibroblasts). 38,43 In this study, the flexibility of the amniotic membrane ensured a tight fit to the liver surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 Our previous study also confirmed that the amniotic membrane extract contains multiple growth factors, including hepatocyte growth factor, epidermal growth factor, etc, which have protective effects on islet survival and function. 20 Therefore, compared with other prevascularization strategies, islet transplantation into PST on the liver surface may be independent of the additional administration of expensive growth factors 39,41,42 or other accessory cells (such as autologous adipose-derived stem cells or fibroblasts). 38,43 In this study, the flexibility of the amniotic membrane ensured a tight fit to the liver surface.…”
Section: Discussionmentioning
confidence: 99%
“…The selection criteria for participants and the written informed consent signing process were the same as described previously. 20…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the immunosuppressive regimen reported from Edmonton, Canada, has achieved unprecedented success in achieving insulin independence in islet transplantation ( 3 ), there are still some problems that affect the outcome of islet transplantation. Advancements in the acquisition of pancreatic islets, immunosuppression of islet recipients, and an increase in the number of transplanted islets are required ( 4 ). The average human pancreas has 300,000 to 1.5 million pancreatic islets, and only 60% of this islet cell mass is needed to maintain a normal glucose metabolism ( 5 ).…”
Section: Introductionmentioning
confidence: 99%